Incidence and risk factors of acute kidney injury associated with continuous intravenous high-dose vancomycin in critically ill patients: A retrospective cohort study. Issue 7 (February 2017) - Lacave, Guillaume; Caille, Vincent; Bruneel, Fabrice; Palette, Catherine; Legriel, Stéphane; Grimaldi, David; Eurin, Mathilde; Bedos, Jean-Pierre
Abstract : Abstract: For vancomycin therapy of severe infections, the Infectious Diseases Society of America recommends high vancomycin trough levels, whose potential for inducing nephrotoxicity is controversial. We evaluated the incidence and risk factors of acute kidney injury (AKI) in critically ill patients given continuous intravenous vancomycin with target serum vancomycin levels of 20 to 30 mg/L. We retrospectively studied 107 continuous intravenous vancomycin treatments of ≥48 hours' duration with at least 2 serum vancomycin levels ≥20 mg/L in critically ill patients. Nephrotoxicity was defined according to the Kidney Disease Improving Global Outcomes Clinical Practice Guideline for AKI (ie, serum creatinine elevation by ≥26.5 μmoL/L or to ≥1.5 times baseline). Risk factors for AKI were identified by univariate and multivariate analyses. AKI developed in 31 (29%) courses. Higher serum vancomycin levels were associated with AKI ( P  < 0.01). Factors independently associated with AKI were highest serum vancomycin ≥40 mg/L (odds ratio [OR], 3.75; 95% confidence interval [CI], 1.40–10.37; P  < 0.01), higher cumulative number of organ failures (OR, 2.63 95%CI, 1.42–5.31; P  < 0.01), and cirrhosis of the liver (OR, 5.58; 95%CI, 1.08–31.59; P  = 0.04). In this study, 29% of critically ill patients had AKI develop during continuous intravenous vancomycin therapy targeting serum levels of 20 to 30 mg/L. Serum vancomycin level ≥40 mg/L was independently associated with AKI.